Asphalt Binder Aging Methods to Accurately Reflect Mixture Aging - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Asphalt binders experience aging that occurs in two distinct stages under quite different conditions: (1) short-term during construction (plant mixing, storage, placement, and compaction) and (2) long-term during the service life of the pavement.The TRB National Cooperative Highway Research Program's NCHRP Research Report 967: Asphalt Binder Aging Methods to Accurately Reflect Mixture Aging documents research conducted to improve laboratory binder conditioning methods to accurately simulate the short-term and long-term aging of asphalt binders, and to calibrate the improved procedures to the aging that occur during mixture production, transport, and placement as well as during the service life of the pavement structure.
Keywords: Transportation and Infrastructure

Innovative Practices for Transit Planning at Small to Mid-Sized Agencies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Diverse small and mid-sized transit agencies are very interested in finding solutions for their transit planning challenges. They will benefit from seeing how similar agencies deal with their transit service issues. Large transit agencies could also apply what is learned to sub-areas in their transit service area that are comparable to the service area of a small or mid-sized transit agency.The TRB Transit Cooperative Research Program's TCRP Synthesis 154: Innovative Practices for Transit Planning at Small to Mid-Sized Agencies documents innovative practices for solving transit planning challenges faced by small and mid-sized transit agencies. These challenges include but are not limited to concerns about ridership, demographic shifts, first- and last-mile transportation, changes in land use, changes in regulations, service design, funding challenges, service delivery, and technology changes. These challenges are applicable to fixed-route, flex-route, and demand-responsive transit services.
Keywords: Transportation and Infrastructure

Guidance to Predict and Mitigate Dynamic Hydroplaning on Roadways - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Hydroplaning is a serious problem that is associated with a relatively small but significant number of crashes. Statistics from various parts of the world indicate that approximately 15% to 20% of all road traffic crashes occur in wet weather conditions.The TRB National Cooperative Highway Research Program's NCHRP Web-Only Document 300: Guidance to Predict and Mitigate Dynamic Hydroplaning on Roadways provides a novel, transformational approach to estimate hydroplaning based on the physics behind it. Using advanced fluid dynamics, tire, and vehicle response models, the project has developed a new way to assess the safety risks associated with vehicle hydroplaning. This research represents one of the first attempts to significantly upgrade understanding and methods to predict hydroplaning potential since the 1970s.Supplemental to the document is a Hydroplaning Potential Assessment Tool and Excel files.
Keywords: Transportation and Infrastructure

Mitigation of Weldment Cracking in Steel Highway Structures Due to the Galvanizing Process - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Structural supports for signs, luminaires, and traffic signals and other steel highway structures are generally galvanized to prevent corrosion and provide a long service life. However, recent investigations have revealed incidents of cracking in weldments of galvanized structures that appear to be induced during the galvanizing process.The TRB National Cooperative Highway Research Program's NCHRP Research Report 965: Mitigation of Weldment Cracking in Steel Highway Structures Due to the Galvanizing Process proposes improved design, materials, and construction specifications of galvanized steel highway structures to mitigate weldment cracking caused by the galvanizing process.Supplemental materials to the report are appendices that provide details of the work performed in the project.
Keywords: Transportation and Infrastructure

Transportation System Resilience: Research Roadmap and White Papers - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Although the need for a more effective set of short- and long-term transportation resilience strategies is increasingly obvious and urgent, many knowledge gaps and institutional barriers still exist.The TRB National Cooperative Highway Research Program's NCHRP Research Report 975: Transportation System Resilience: Research Roadmap and White Papers highlights significant knowledge gaps within AASHTO and state departments of transportation, presents a 5-year research plan that addresses these gaps, and discusses critical resilience-related issues facing senior transportation leaders today.Supplementary materials to the report include a Road Map Ratings and Rankings Workbook (Appendix B) and a Resilience Research Roadmap and White Papers Presentation.
Keywords: Transportation and Infrastructure

Evaluation and Synthesis of Connected Vehicle Communication Technologies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
In 1999, the Federal Communications Commission (FCC) allocated the intelligent transportation system (ITS) band, also known as the “5.9 GHz band,” for transportation purposes including connected and automated vehicle (CAV) technologies. These technologies enable a host of applications for vehicle‐to-vehicle, vehicle‐to‐infrastructure, and vehicle‐to‐pedestrian communication — collectively known as vehicle‐to‐everything (V2X). Today, the connectivity required for V2X is enabled by dedicated short‐range communications and cellular V2X.The TRB National Cooperative Highway Research Program's NCHRP Web-Only Document 310: Evaluation and Synthesis of Connected Vehicle Communication Technologies presents a compilation of material on the 5.9 GHz band and the actions taken by the FCC from 2019 through early 2021 to reallocate portions of this band away from dedicated use for traffic flow, traffic safety, and other ITS applications that are essential for CAVs.Supplementary to the document is a video.
Keywords: Transportation and Infrastructure

Protocols for Network-Level Macrotexture Measurement - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Macrotexture, which influences vehicle-roadway skid resistance, refers to the texture of the pavement due to the arrangement of aggregate particles. Pavement surfaces are subjected to seasonal variations, and over time the embedded aggregates become polished due to the onslaught of traffic. Research has shown that wet-weather crashes are influenced by the macrotexture of the pavement surface.The TRB National Cooperative Highway Research Program's NCHRP Research Report 964: Protocols for Network-Level Macrotexture Measurement provides state transportation pavement engineers and other practitioners with recommended protocols for macrotexture test measures, equipment specifications, and data quality assurance practices.
Keywords: Transportation and Infrastructure

Practices for Bridge Approach Systems - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Bridge approach systems are used by state departments of transportation (DOTs) to form a smooth transition between the roadway and bridges. Adequate performance of bridge approaches is of extreme importance to transportation agencies as they affect both safety and the public perception of ride quality if the transition is not smooth.The TRB National Cooperative Highway Research Program's NCHRP Synthesis 566: Practices for Bridge Approach Systems documents the current state of the practice at state DOTs related to the design, construction, and maintenance of bridge approach systems. State DOT design guides and standard specifications were reviewed as part of the information-gathering process.
Keywords: Transportation and Infrastructure

Transit Agency Relationships and Initiatives to Improve Bus Stops and Pedestrian Access - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
In the United States, many transit stops are not adequate: bus stops that are just a signpost on a busy road, bus stops with broken sidewalks and/or pathway obstructions, bus stops with a lack of seating, and bus stops clearly not accessible to people with disabilities. For many bus riders, the journey to access and the wait at the bus stop are experiences that may inhibit their ability or desire to take the bus.The TRB Transit Cooperative Research Program's TCRP Synthesis 152 Transit Agency Relationships and Initiatives to Improve Bus Stops and Pedestrian Access summarizes the current state of practice for bus stop and pedestrian infrastructure improvement programs and processes in place at transit agencies and other public organizations.
Keywords: Transportation and Infrastructure

Mainstreaming System Resilience Concepts into Transportation Agencies: A Guide - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Transportation officials recognize that a reliable and sustainable transportation system is needed to fulfill their agency’s mission and goals.The TRB National Cooperative Highway Research Program's NCHRP Research Report 970: Mainstreaming System Resilience Concepts into Transportation Agencies: A Guide provides transportation officials with a self-assessment tool to assess the current status of an agency’s efforts to improve the resilience of the transportation system through the mainstreaming of resilience concepts into agency decision-making and procedures. The tool can be applied to a broad array of natural and human-caused threats to transportation systems and services. The report is related to NCHRP Web-Only Document 293: Deploying Transportation Resilience Practices in State DOTS. Supplemental materials to the report include a Posters Compilation and the Program Agenda from the 2018 Transportation Resilience Innovations Summit and Exchange, and a PowerPoint Presentation on resilience.
Keywords: Transportation and Infrastructure

Criteria for Restoration of Longitudinal Barriers, Phase II - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Guardrails are an important feature of the roadside that are used to shield errant motorists from becoming involved in even more catastrophic crashes by redirecting vehicles away from fixed hazards such as trees and poles and terrain hazards such as steep roadside slopes and fill embankments.The TRB National Cooperative Highway Research Program's NCHRP Web-Only Document 304: Criteria for Restoration of Longitudinal Barriers, Phase II develops a Field Guide to assist maintenance personnel in making decisions about repairing damaged guardrail installations.Supplementary material to the document is Appendices A-S.
Keywords: Transportation and Infrastructure

A Pandemic Playbook for Transportation Agencies - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Understanding pandemics, their impacts to transportation, and potential effective response has become more important, not only for the response to COVID-19, but also if, as the World Health Organization warns, we are now “living in a time of viruses.”TRB's National Cooperative Highway Research Program and Transit Cooperative Research Program have jointly issued NCHRP Research Report 963/TCRP Research Report 225: A Pandemic Playbook for Transportation Agencies, which was created to improve transportation agency responses to a pandemic.The Playbook concentrates on what needs to be done, when and by whom. It briefly addresses planning for a pandemic, a topic addressed in greater depth in NCHRP Report 769: A Guide for Public Transportation Pandemic Planning and Response. It summarizes effective practices currently used by transportation agencies based on interviews with state departments of transportation and transit agency leaders and operational personnel, supplemented with national and international research results.
Keywords: Transportation and Infrastructure

Validation of a Performance-Based Mix Design Method for Porous Friction Courses - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Porous Friction Course (PFC) mixtures are designed with an open aggregate structure to yield high inplace air voids (i.e., typically between 15 and 20 percent). This allows rainwater to drain horizontally through the layer toward the edge of the pavement structure, thereby improving pavement surface friction.The TRB National Cooperative Highway Research Program's NCHRP Web-Only Document 305: Validation of a Performance-Based Mix Design Method for Porous Friction Courses is designed to assist state highway agencies in implementing the proposed performance-based mix design procedure, verify if the thresholds proposed in the procedure could be achieved, and refine the procedure if needed.
Keywords: Transportation and Infrastructure

Redesigning Transit Networks for the New Mobility Future - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Urban travel patterns are affected by many factors including changes in demography, land use, economics, technology, and mobility options. Public transportation must evolve to remain responsive.The TRB Transit Cooperative Research Program's TCRP Research Report 221: Redesigning Transit Networks for the New Mobility Future presents case studies and toolkits to plan and implement the redesign of bus networks in the United States.
Keywords: Transportation and Infrastructure

Transit and Micromobility - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Micromobility refers to small, low-speed vehicles intended for personal use and includes station-based bikeshare systems, dockless bikeshare systems, electric-assist bikeshare, and electric scooters. Micromobility has the potential to increase the number of transit trips by expanding the reach of multimodal transportation, but it also could replace transit trips.The TRB Transit Cooperative Research Program's TCRP Research Report 230: Transit and Micromobility provides an analysis of the full benefits and impacts of micromobility on public transportation systems in transit-rich markets as well as in medium-sized and smaller urban areas.
Keywords: Transportation and Infrastructure

Entrained Air-Void Systems for Durable Highway Concrete - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Laboratory testing and field experience have shown that highway concrete should be properly air entrained to resist the action of freezing and thawing, particularly in wet climates. Several gaps in the state of the knowledge still exist.The TRB National Cooperative Highway Research Program's NCHRP Research Report 961: Entrained Air-Void Systems for Durable Highway Concrete addresses these gaps and, more specifically, investigates innovative test methods for effectively characterizing the air system in fresh concrete and identifying the characteristics of the air-void system that are related to the performance of field concrete under freeze-thaw conditions.Appendices A –G provide further details on the different aspects of the research performed for this project.• Appendix A: Test: Matrix for Laboratory Mixtures• Appendix B: Petrographic Analysis Report• Appendix C: Appendix C Data Obtained from Testing Concrete Mixtures Produced in the Laboratory• Appendix D: Appendix D Flatbed Scanner Threshold Optimization Details and Test Results• Appendix E: Clustering Analysis Test Results• Appendix F: Microcomputer Control for AASHTO T 161 “A” Freeze–Thaw• Appendix G: Data Obtained During F-T Testing
Keywords: Transportation and Infrastructure

Long-Term Aging of Asphalt Mixtures for Performance Testing and Prediction: Phase III Results - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The accurate characterization of the in situ aging of asphalt pavement materials over the service life of the pavement is of utmost importance to the implementation of mechanistic empirical (ME) pavement design and analysis methods.The TRB National Cooperative Highway Research Program's NCHRP Research Report 973: Long-Term Aging of Asphalt Mixtures for Performance Testing and Prediction: Phase III Results refines the aging procedure developed in the original NCHRP Research Report 871: Long-Term Aging of Asphalt Mixtures for Performance Testing and Prediction. The updates field calibrate the original project aging model (PAM), develop procedures to estimate the PAM inputs, and develop a framework by which the predicted changes in asphalt binder properties that are due to oxidative aging can be related to corresponding changes in asphalt mixture performance.
Keywords: Transportation and Infrastructure

Legal Implications of Data Collection at Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
As technology evolves, airports and their partners collect more data from passengers, employees, tenants, concessionaires, airlines, and others. This data is used in many ways, including for facility management, security, ground transportation, marketing, understanding passenger preferences, and enhancing the travel experience.The TRB Airport Cooperative Research Program's ACRP Legal Research Digest 42: Legal Implications of Data Collection at Airports provides a survey of applicable law; considerations for the collection and safekeeping of data; and a review of the issues that arise related to data collection among airports, their tenants, and other users. It also offers an understanding of the expansion in law around data collection and use.
Keywords: Transportation and Infrastructure

Options for Reducing Lead Emissions from Piston-Engine Aircraft - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Small gasoline-powered aircraft are the single largest emitter of lead in the United States, as other major emission sources such as automobile gasoline have been previously addressed. A highly toxic substance that can result in an array of negative health effects in humans, lead is added to aviation gasoline to meet the performance and safety requirements of a sizable portion of the country’s gasoline-powered aircraft.Significantly reducing lead emissions from gasoline-powered aircraft will require the leadership and strategic guidance of the Federal Aviation Administration (FAA) and a broad-based and sustained commitment by other government agencies and the nation’s pilots, airport managers, aviation fuel and service suppliers, and aircraft manufacturers, according to a congressionally mandated report from the National Academies of Sciences, Engineering, and Medicine.While efforts are underway to develop an unleaded aviation fuel that can be used by the entire gasoline-powered fleet, the uncertainty of success means that other steps should also be taken to begin reducing lead emissions and exposures, notes the report, titled TRB Special Report 336: Options for Reducing Lead Emissions from Piston-Engine Aircraft.Piston-engine aircraft are critical to performing general aviation (GA) functions like aerial observation, medical airlift, pilot training, and business transport. Other GA functions, such as crop dusting, aerial firefighting, search and rescue, and air taxi service, have particular significance to communities in rural and remote locations.Accompanying the report is a three-page highlight summary that provides a condensed version of the findings.
Keywords: Transportation and Infrastructure

Technical Feasibility of a Wheelchair Securement Concept for Airline Travel: A Preliminary Assessment - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
There appear to be, in this preliminary assessment, no formidable issues that present design and engineering challenges for installing in-cabin wheelchair securement systems in airplanes. While equipping enough airplanes with securement systems to provide meaningful levels of airline service would require substantial effort, the types of cabin modifications required to provide the needed space and structural support would likely be of moderate technical complexity for many individual airplanes.TRB’s Special Report 341: Technical Feasibility of a Wheelchair Securement Concept for Airline Travel: A Preliminary Assessment identifies and examines potential technical challenges to the development and implementation of an in-cabin wheelchair securement system.
Keywords: Transportation and Infrastructure